Comparative Analysis of Grab, Conveyor, and Excavator Unloading Equipment on Time Efficiency and Port Costs in Bulk Urea Fertilizer Unloading at Tanjung Emas Port, Semarang - Mulki Jasty Amanda; Sutini; Dedy Rusmiyanto; Zihni Ihkamuddin (Ambidextrous Journal of Innovation Efficiency and Technology in Organization, 2026)
This study aims to analyze the performance and port cost efficiency of bulk urea fertilizer unloading operations at Tanjung Emas Port, Semarang, by comparing three types of unloading equipment: conveyor, grab, and excavator. Data were collected through direct observation and documentation of operations on MV Soemantri Brodjonegoro (conveyor), MV Pusri Indonesia 1 (grab), and TB Del 02/BG Parta Jaya 3006 (excavator) during March–May 2025. Parameters measured include unloading productivity (MT/hour), effective berthing time, downtime percentage, and total port costs (berthage, pilotage, towage, unloading charges) based on Minister of Transportation Regulation No. PM 10 of 2021. Results show that the conveyor achieved the highest productivity at 109.79 MT/hour, followed by excavator at 104.156 MT/hour and grab at 101.006 MT/hour. The grab recorded the lowest downtime percentage (12%), while conveyor (19%) and excavator (18%) were higher. In terms of port cost, excavator was the most economical (IDR 21,549,045), followed by conveyor (IDR 25,337,476), with grab the highest (IDR 29,874,552). Unloading charges dominated more than 74% of total costs across all three methods. These findings provide strategic guidance in selecting unloading equipment based on operational priorities, whether speed or cost efficiency.